Enmity Reflected in J. K. Rowlings The Casual Vacancy (2012): an Individual Psychological Approach - FATIMAH, FITRI, Dr. Phil. Dewi Candraningrum. M. Ed, Titis Setyabudi, S.S. M. Hum (2016)
The major problem of this study is enmity. Some people have conflict, they have enmity to fight the empty seat on the Paris Council. They must do the efforts to get the vacancy chair. The objective of this study is to analyze this novel based on the Individual Psychological Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data sources of the study in The Casual Vacancy novel by J.K Rowling. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclutions. The study shows that the problem faced by the major characters are their enmity. These are proven by their passion that becomes the member on the Parish Council. They are Colin Wall, Simon Price, and Miles Mollison. they want to be successful person. They use their ability to manage their strategy. They should make every effort to get the vacancy chair on the Parish Council.